Bohaterki indyjskich mitów i legend w pisarstwie autobiograficznym kobiet w hindi - Browarczyk, Monika (Gajt Wydawnictwo 1991 s.c., 2018)
Drawing from Gayatri Spivak’s (1989: 227) reflections on mythological figures as ‚regulative psychobiographies’, the article attempts a look at heroines of Indian myths and legends in selected Hindi autobiographies by women i.e. Krishna Agnihotri’s Lagtā nahī̃ hai dil mera (1996) and Aur, aur... aurat (2010); Maitreyi Pushpa’s Kasturī kuṇḍal basai (2002) and Guṛiyā bhītar guṛiyā (2008); Prabha Khaitan’s Anyā se ananyā (2007) and Kausalya Baisantri’s Dohrā abhiśāp (1999). The cohort of analysed heroines includes symbols of feminine power and fierce independence (like Śakti, Durgā, Maitreyī, Āmrapālī or Draupadī) and ideals of submissiveness, faithfulness and obedience (e.g. Sītā, Damayantī, Sāvitrī or Sātī). These symbolical figures dictate or contradict Indian cultural constructs of womanhood; therefore their presence, or absence, in autobiographical writings by women is a crucial element of narrative strategies employed by them.
Keywords: Hindi autobiographies; women writing; Krishna Agnihotri; Maitreyi Pushpa; Prabha Khaitan; Kausalya Baisantri; Śakti; Durga; Majtreji; Amrapali Draupadi; Sita Damajanti; Sawitri; Sati